Kewenangan Lembaga Adat dan Pemerintahan Nagari di Nagari Balimbing, Kecamatan Rambatan, Kabupaten Tanah Datar, Sumatera Barat. - Gushamenri -; Kushanjani -; wahid abdurrahman (Journal of Politic and Government Studies, 2018)
Government policy on village governance since the beginning of independence until now has always changed. In the year 1948 - 1965 applies Law no. 22 of 1948 which allowed the village as a third-level area, from 1965 to 1979 Law no. 19 of 1965 on decentralization, and in 1979 - 1999 Law no. 5 of 1979 which regulates village uniformity. Furthermore, in the reform era regulated in Law no. 22 of 1999 on Regional Government and the latest Law no. 6 of 2014 on the Village.After the Orde Baru era, the village administration was uniformed into an administrative village, in the era of the Reformation rolling West Sumatera Provincial Government issued Local Regulation no. 9 Year 2000 to restore the lowest government in West Sumatra the form of nagari or adat village. the policy of returning to the Nagari Government led to an institutional dualism in Nagari. So this study explains about the authority of customary institutions and Nagari Government in Nagari Balimbing, District Rambatan, Tanah Datar regency, West Sumatra.This study aims to provide a description of the institutional authority and the Nagari Government. The theory used in this research is the theory of village autonomy and authority of traditional village. The type of research used is qualitative-descriptive research type. Primary data source in this research is produced through interviews conducted with informants using purposive sampling technique. Data analysis techniques used are data reduction, presentation and draw conclusions .From the research result, it is known that the authority of customary institutions in nagari has changed. Changes arose due to village uniformity through Law no. 9 of 1979. The conclusion of this study is that the authority of Nagari Traditional Institution is shifting due to the changing government regulations on the village.Keyword: Authority, Customary Institutions, Nagari Government